Odyssey Self Reflection - Set makeup / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
The beauty of makeup is the concept of my artwork which is reflecting my self-confident. The elements consisted of my artworks are highlighting to the form of Makeup set, warm and cool colour and space. I used unwanted materials for my sculpture such as wood, makeup items, button and plywood. I used the stencil technique in my printmaking.